Leukocyte dynamics in Cynomolgus monkeys following heterotopic heart allotransplantation under costimulation pathway blockade - Braileanu, Gheorghe; Azimzadeh, Agnes M.; Zhang, Tianshu; Burdorf, Lars; Pierson III, Richard N. (Frontiers in Immunology, 2025)
RationaleIt was hypothesized that the dynamics of leukocyte populations in peripheral blood (PB) or peri-graft lymph nodes (LNs) in cynomolgus monkey recipients of a heterotopic heart allotransplant, completed with the determination of graft-infiltrating lymphocyte (GIL) populations at explant, may vary in association with immune rejection mechanisms or immunomodulatory treatments.MethodsAmong 15 cynomolgus monkey recipients of heterotopic heart allografts, 13 were treated with a variety of costimulation-blocking immunosuppressive (IS) agents targeting CD80/CD86, CD28, CD40, or CD154, and two were untreated (controls). Leukocyte populations were characterized using hemocytometry and flow cytometry.ResultsIn PB, neutrophils and monocytes increased significantly (p < 0.001) during the first 2 weeks after transplant. Eosinophils and monocytes steadily increased after transplant, peaking around the time of graft failure (p < 0.01), a trend most prominent in association with belatacept. After the initial nadir on day 1 after transplant, PB lymphocytes increased steadily, particularly in association with belatacept and hu5c8, to a peak 1 week before graft rejection (p < 0.05), like CD3 cells. In PB, the CD4/CD8 ratio consistently trended down in all treated groups, most prominently in association with 5c8. In LNs at explant, CD4 cells outnumbered CD8 cells (p < 0.001), whereas in graft-infiltrating lymphocytes (GILs), CD8 cells predominated (p < 0.001). Among GILs at the time of rejection, CD8+CD62− central and effector memory cells were prominent, along with CD4+CD8+ T cells and IgD−CD27− B cells. At explant time, analysis of CD3 CD127lowCD25highFoxp3+ cell populations identified in GILs two clusters of CD4+CD8+ and three clusters of CD8 cells, which were expanded relative to PB or LNs.ConclusionsObservations regarding CD8 T-cell subpopulations in PB, LNs, and GILs support the conventional paradigm regarding their role as key effector cells mediating graft injury. The prominence of CD4+CD8+CD127lowCD25highFoxp3+ T cells and that of IgD−CD27− B cells among GILs have not previously been described. Expansion of circulating eosinophils around the time of rejection may implicate these cells in rejection mechanisms. Comparison of graft lymphocyte subpopulations with LNs or PB highlights mechanistically plausible differences that justify further efforts to elucidate their roles in graft injury and protection as a strategy to identify new candidate approaches to prevent rejection and promote tolerance.